2016
DOI: 10.1080/15685551.2016.1231048
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of G0 aminopolyol and aminosugar dendrimers, controlled by NMR and MALDI TOF mass spectrometry

Abstract: Organic compounds designed to serve as stable dendrimer cores were developed. A series of aminosugar and amino polyol containing G0 dendrimers were synthesized. The reaction mixture composition was checked by MALDI TOF mass spectrometry, while that of purified products – by 1H and 13C NMR combined with 2D NMR spectroscopy as well as MALDI TOF MSMS mass spectra. Mass spectrometric fragmentation experiments were performed in positive ion mode in order to determine common fragmentation patterns of [M+H]+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…28. [85][86][87] A summary of selected types of dendrimers and applications referenced is found in Table 1 below.…”
Section: Glycoside-based Dendrimersmentioning
confidence: 99%
“…28. [85][86][87] A summary of selected types of dendrimers and applications referenced is found in Table 1 below.…”
Section: Glycoside-based Dendrimersmentioning
confidence: 99%
“…Despite the widespread use of EP for βCD cross-linking, its toxicity and carcinogenicity have been documented, , rendering it unsuitable for water treatment applications. Consequently, alternative and more biocompatible cross-linkers have been reported in the literature for βCD cross-linking. Triphenylolmethane triglycidyl ether (TMTE) and trimethylolpropane triglycidyl ether (TPTE) have been selected in this study as alternative cross-linkers based on characteristics of lower toxicity, commercial availability, and similar epoxy groups suitable for cross-linking reactions, as present in EP. TMTE and TPTE have been reported as cross-linkers in biomaterials including dental materials and drug delivery materials. , Chung et al reported TMTE cross-linked photocurable material that aimed to be applied in dental applications showing low curing shrinkage, low water sorption, and low water solubility. Suner et al reported the biomaterials containing TPTE, which showed fast enzymatic degradation of 80–90% using pectinase and amyloglucosidase.…”
Section: Introductionmentioning
confidence: 99%